ANALISIS KESESUAIAN LANSKAP FULAN FENAN SEBAGAI OBJEK WISATA SEJARAH YANG BERKELANJUTAN - Debora Budiyono; Hendra Kurniawan; Astri Sumiati; Yohanes Delvianus Assa (Universitas Tribhuwana Tunggadewi, 2022)
The Fulan Fehan area located in Dirun Village, Lamaknen District, Belu Regency, East Nusa Tenggara Province. The Fulan Feran area has beautiful natural potential expanses of meadows, cactus plants, and livestock grazing areas. While cultural values such as several makes forts inherited from the Portuguese and menhirs or offering tables, stone graves. The existence of Fulan Fehan area has the potential as a tourist attraction. Fulan Fehan area is one of the historical tourist destinations however, it develops without considering land suitability. The aimed of this study was to analyze the land suitability of the Fulan Fehan landscape as a sustainable historical tourism object. The method used is field observation and Focus Group Discussion (FGD) with the Dirun Village community. Data analysis was carried out spatially through a Geographic Information System (GIS), namely physical, history, objects and attractions, and visual landscapes. The results showed that the suitability of the landscape of the historical tourist area of Fulan Fehan is very suitable (SS) has an area of 149.62 ha (78.78%), quite suitables (CS) has an area of 25.99 ha (13.69%), and less suitable (KS) which has an area of 14.31 ha (7.53%). Suitability analysis of tourism and FGDs showed that Fulan Fehan has potential to develop sustainable historical tourism.